Design and preparation of poly(aryl ether ketone)/phosphotungstic acid hybrid films with low dielectric constant. Issue 6 (20th February 2013) - Geng, Zhi; Zhang, Shuling; Mu, Jianxin; Jiang, Xu; Huo, Pengfei; Lu, Yaning; Luan, Jiashuang; Wang, Guibin
Abstract A material with low dielectric constant was produced using nanoparticle phosphotungstic acid (PWA) modified by the silane coupling agent γ‐aminopropyltriethoxysilane (KH‐550) dispersed in a poly(aryl ether ketone) containing (3‐trifluoromethyl) phenyl side groups (FPEEK) matrix synthesized with (3‐trifluoromethyl) phenyl hydroquinone (3FHQ) and 4, 4′‐difluorobenzophenone. The material was fabricated using solution‐blending. Moreover, the dielectric, thermal, and mechanical properties of this material were characterized using a precision impedance analyzer, thermal gravimetric analyzer, and universal tester, respectively. The results indicate that modified PWA (m‐PWA)/FPEEK composites show obvious improvement in the dielectric properties compared to unmodified PWA (p‐PWA)/FPEEK composites. This should be attributed to the good dispersion and compatibility of m‐PWA in FPEEK, as proven by scanning electron microscope and wide‐angle X‐ray diffraction. Besides, m‐PWA/FPEEK composites also exhibited the relatively good thermal and mechanical properties. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013